MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS VI PADA MATA PELAJARAN IPS DENGAN MENGGUNAKAN MEDIA PETA DAN GLOBE DI SD NEGERI NAPUNGBIRI PANTE - Karolus Keson Ritan (Yayasan Akrab Pekanbaru, 2019)
The purpose of this study is to improve that the use of map and globe media can improve the learning activeness of Grade VI students at SD Negeri Napungbiri Pante in the academic year 2017/2018. Data collection techniques using the method of interviews, observation, field notes and documentation. Based on the results of the study showed an increase in the activeness and learning outcomes of students in social studies learning. This can be seen from the activity of students in each cycle, the initial conditions were 32.72%, increased by 53.63% in the first cycle of the first cycle, increased by 82.72% in the first cycle of the second round. Then in Cycle II also experienced an increase in the first round of 86.16%, in the second round it increased 92.45%. And learning outcomes in the initial conditions 29.41% experienced an increase of 47.05% in the first cycle of the first round and 70.58% in the first cycle of the second round. Then in the first cycle of the second cycle 82.35%, increased to 94.11% in the second cycle of the second round. Thus, from this study, it can be concluded that the use of map and globe media can increase the activeness and learning outcomes of students in social studies learning in the sixth grade students of SD Negeri Napungbiri in the 2017/2018 Academic Year.